2019
DOI: 10.1002/jcb.29375
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA inhibits the adipogenesis and inflammatory response in ox‐LDL‐challenged human monocyte‐derived macrophages via regulating miR‐130b/WNT5A

Abstract: Atherosclerosis is a kind of chronic cardiovascular disease, characterized by oxidized low‐density lipoprotein (ox‐LDL) accumulation in macrophage. Tanshinone IIA (Tan), a lipophilic pharmacologically activate compound from Salvia miltiorrhiza Bunge, has been indicated to exert cardioprotective roles. Nevertheless, the biological role of Tan and regulatory mechanism in atherosclerosis are not fully established. In present study, atherosclerosis model was established in THP‐1‐derived macrophages by treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Tanshinone IIA, an active compound, has multiple pharmacological functions, such as anti-inflammation and antioxidation. After the exposure of Tanshinone IIA to atherosclerosis model which is established by THP-1-derived macrophages treated with ox-LDL, the expression of IL-1β, IL6, and TNF-α was decreased compared to the untreated group, and a further study revealed that Tanshinone IIA may decrease the inflammatory response by mediating miR-130b and WNT5A [47]. In this study, our results showed that CCL2 significantly upregulated the expression of IL-1β and IL-6 in hippocampi of rats, while the expression of IL-1β and IL-6 in hippocampi of rats pretreated with Tan IIA decreased.…”
Section: Discussionmentioning
confidence: 94%
“…Tanshinone IIA, an active compound, has multiple pharmacological functions, such as anti-inflammation and antioxidation. After the exposure of Tanshinone IIA to atherosclerosis model which is established by THP-1-derived macrophages treated with ox-LDL, the expression of IL-1β, IL6, and TNF-α was decreased compared to the untreated group, and a further study revealed that Tanshinone IIA may decrease the inflammatory response by mediating miR-130b and WNT5A [47]. In this study, our results showed that CCL2 significantly upregulated the expression of IL-1β and IL-6 in hippocampi of rats, while the expression of IL-1β and IL-6 in hippocampi of rats pretreated with Tan IIA decreased.…”
Section: Discussionmentioning
confidence: 94%
“…It plays a leading role in the occurrence and development of systemic inflammation. In the early stage of sepsis, a large amount of TNF-α is mainly produced by macrophages and neutrophils, and it is the initiator in the cascade reaction process of inflammatory mediators (Mokotedi et al, 2019;Xue et al, 2019;Yuan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Tan had varied biological capabilities, such as anti-oxidation, anti-apoptosis, anti-in ammation, anti-cancer, improving microcirculation, and anti-myocardial ischemia [26]. Yet, the molecular system allows Tan connected with atheroprotection is inadequately identi ed [4].…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine shows an imperative in uence on the medical treatment of people, which acts as athero-protectors [4]. Tanshinones are the main e cient elements of the Chinese medicinal herb Salvia miltiorrhiza, also known as Danshen, which has been extensively utilized in Asian nations to avert and manage malignant tumors, in ammatory diseases and CVD [5].…”
Section: Introductionmentioning
confidence: 99%